PEMBELAJARAN BAHASA ASING DI INDONESIA: ANTARA GLOBALISASI DAN HEGEMONI - Santoso, Iman (Jurnal Pendidikan Bahasa dan Sastra, 2014)
Foreign language learning in Indonesia constitutes an attempt for Indonesians to be able to absorp and keep up with the development of science and technology in the world, and to provide a way for Indonesian people to interact with other global members. On the other hand, there appears some concern that there may be infiltration of foreign values, especially from the West, that might weaken the learners‘ identities as Indonesians. This concern has emerged because foreign language learning generally presents Western elements of cultures and values. If it is not critically examined, these Western values are likely to change the learners‘ points of view of cultural values appropriate to be practised in their lives. Foreign language learning is also suspected as a means for the West to extend the Western hegemonies over the East such as Indonesians. This article explores a number of issues: (i) learning situations of foreign languages in Indonesia, (ii) Western hegemonic forms over the Eastern world through foreign language learning and (iii) alternative forms of foreign language learning based on ethnopedagogic and intercultural values.